2014
DOI: 10.1111/adj.12165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological characterization of localized aggressive periodontitis: a cohort study

Abstract: Background: Localized aggressive periodontitis (LAgP) is an infectious periodontal disease which generally affects young people. Recent data suggest the involvement of different bacterial species in different populations. The causative bacterial species in Israel has never been identified despite a high prevalence of LAgP in this population. The objectives of this study were to characterize the bacterial microbiota of periodontal pockets within an Israeli LAgP population who were also clinically assessed. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
2
7
0
1
Order By: Relevance
“…Comparing AP and CP, more positive results of A. actinomycetemcomitans and E. nodatum were found in AP patients. Regarding A. actinomycetemcomitans, this finding confirms those of a recent study where about 70% of positive samples were detected in patients diagnosed with localized AP [30]. In our study, half of the AP patients have been tested positively for A. actinomycetemcomitans.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing AP and CP, more positive results of A. actinomycetemcomitans and E. nodatum were found in AP patients. Regarding A. actinomycetemcomitans, this finding confirms those of a recent study where about 70% of positive samples were detected in patients diagnosed with localized AP [30]. In our study, half of the AP patients have been tested positively for A. actinomycetemcomitans.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, F. nucleatum recently has been implicated as a potential target pathogen (26). F. nucleatum also is prevalent within deep periodontal pockets of LAP patients (27), and its abundance in the biofilm is associated with the severity of periodontal inflammation in adolescents (28). In addition, F. nucleatum is essential for the growth of P. gingivalis and A. actinomycetemcomitans (29), and it can synergistically create a stronger inflammatory response with more tissue destruction in coinfections with P. gingivalis in a mouse periodontitis model (30).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from 1998 forward examined a broad spectrum of bacteria using DNA technologies (Table ) . In one‐half the studies Aggregatibacter actinomycetemcomitans was implicated as a risk marker, and in another half Porphyromonas gingivalis , Tannerella forsythia , and Selenomonads emerged as markers of risk (Table ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies from 1998 forward examined a broad spectrum of bacteria using DNA technologies ( Table 2). [23][24][25][26][27][28][29][30][31][32][33][34][35][36] In one-half the studies Aggregatibacter actinomycetemcomitans was implicated as a risk marker, and in another half Porphyromonas gingivalis, 23,25,27,[32][33][34][35] Tannerella forsythia, 27,29,32,34,35 and Selenomonads emerged as markers of risk (Table 2). A recent study 37 showed that in younger individuals A. actinomycetemcomitans was associated with disease whereas this was not the case in older subjects.…”
Section: Relevant Findingsmentioning
confidence: 99%